Opisne značilnosti medvrstniškega nasilja in sorodnih konstruktov v različnih točkah merjenja: preliminarni rezultati raziskave (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Peer violence and victimization are complex phenomena associated with different factors and manifestations. In the present study, we examined some of these factors in a longitudinal study with three measurement points in one school year. The purpose of this paper is to briefly outline the research design used and present the basic descriptive characteristics of the measured constructs, with an emphasis on different forms of violence and victimization. Preliminary results for each measurement point indicate that a large proportion of the variability in the incidence of self-reported violence and victimization can be attributed to individual differences. Between individual measurement points (beginning and end of school work), a small increase in self-reported violence and victimization is detected, but this increase is not very pronounced. This can be partly explained by the sample size, which does not exclude differences at the individual or class level over time.